2016
DOI: 10.3945/jn.115.218354
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives of Personalized Weight Loss Interventions Based on Nutrigenetic, Epigenetic, and Metagenomic Data

Abstract: As obesity has become a major global public health challenge, a large number of studies have analyzed different strategies aimed at inducing a negative energy balance and, consequently, body weight loss. However, most existing weight loss programs are generally unsuccessful, so several interventions have been carried out to identify physiologic and behavioral factors concerning this variability in order to implement more personalized treatment. Nowadays, an individualized approach is being proposed through so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 96 publications
0
44
0
Order By: Relevance
“…In humans, the microbiota composition is usually different in lean and obese people with obese having showed a reduction in Bacteroidetes accompanied by a rise in Firmicutes [34,36,62,63,66,68,93,94]. Evidence shows that some bacteria, particular in the Firmicutes phyla, are better at harvesting energy from the food than other phyla and bacterial species thereby contributing to weight gain [34,65,68,93]. Remely et al [94] also found a significantly higher ratio of Firmicutes and Bacteroidetes in type-2 diabetics compared to lean controls and obese.…”
Section: Global Health Epidemiology and Genomicsmentioning
confidence: 99%
“…In humans, the microbiota composition is usually different in lean and obese people with obese having showed a reduction in Bacteroidetes accompanied by a rise in Firmicutes [34,36,62,63,66,68,93,94]. Evidence shows that some bacteria, particular in the Firmicutes phyla, are better at harvesting energy from the food than other phyla and bacterial species thereby contributing to weight gain [34,65,68,93]. Remely et al [94] also found a significantly higher ratio of Firmicutes and Bacteroidetes in type-2 diabetics compared to lean controls and obese.…”
Section: Global Health Epidemiology and Genomicsmentioning
confidence: 99%
“…Also, it is now recognized that interactions of genetic and epigenetic signatures with environmental factors (dietary intake or physical activity) play an important role in determining individual phenotypes [6,7]. Recent advances in genomic sequencing and large cohort studies are enabling clarification of the involvement and the interplay of these factors in chronic disorders including obesity, which open a new field to customize intervention strategies [8,9]. Precision medicine refers to disease therapeutics based on interindividual differences, such as genetic profile, phenotype, gender, microbiome, and environmental features [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, obesity status is complex and multifactorial, and lifestyle modifications including dietary-induced weight loss and physical activity are not equally effective for every person. Therefore, continuous efforts are being made to develop personalized approaches based on nutrigenetic and nutrigenomic data [3]. Consequently, novel biomarkers of prognosis or even of response to dietary treatments to overcome obesity and its inflammatory state are urgently required.…”
Section: Introductionmentioning
confidence: 99%